2020
DOI: 10.1088/1755-1315/440/5/052041
|View full text |Cite
|
Sign up to set email alerts
|

Application and Development of New Drones in Agriculture

Abstract: With the advancement of technology and advances in technology, the research on drones has become more and more in-depth, and the practical application fields have become more extensive. Its unparalleled advantages also play an important role. At present, drone technology has also gradually Mature. Drones are creating a new agricultural revolution. It is estimated that the size of drones in the agricultural market will reach billions of dollars in the next few years. As editor of the UN Food and Agriculture Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…There is a possibility that crop withering and destroying pathogens evade detection due to the lack of careful inspection. Here comes the role of drones as they can easily distinguish the yellowing plants from the green ones [77]. In a study where drone was used to monitor the canola crop, the mapped region was reported to exhibit reductions in NDVI and leaf area index (LAI) hinting towards its inspection for nutrient deficiency, so that the subsequent pest and disease can be detected beforehand [17].…”
Section: Disease Surveillancementioning
confidence: 99%
See 4 more Smart Citations
“…There is a possibility that crop withering and destroying pathogens evade detection due to the lack of careful inspection. Here comes the role of drones as they can easily distinguish the yellowing plants from the green ones [77]. In a study where drone was used to monitor the canola crop, the mapped region was reported to exhibit reductions in NDVI and leaf area index (LAI) hinting towards its inspection for nutrient deficiency, so that the subsequent pest and disease can be detected beforehand [17].…”
Section: Disease Surveillancementioning
confidence: 99%
“…To effectively assess the topography of the land, farmers can benefit from the laser scanning technology or software capable of stitching hundreds of high-quality aerial imageries into 3D maps. These 3D maps thus generated indicate the water flow direction at the bottom of each tree in the orchard along with the identification of other features [77].…”
Section: Irrigation and Fertilizationmentioning
confidence: 99%
See 3 more Smart Citations